Effect of music on test scores of students in chemistry and accounting - Giita Silverajah, *; Soh, Jason Chiaw Ker * (Sunway College Kuala Lumpur, 2015)
This study examined classical music’s effect on exam performance in a college setting by randomising students to listen to Richard Stoltzman’s Maid with the Flaxen Hair while taking a test for a science and a non-science subject, namely Chemistry as well as Accounting and Finance, respectively. We controlled for: prior knowledge on the subject matter, year in college and age. Findings revealed that there was a slight improvement on Accounting and Finance exam performance when the music was played during the test by a 7.9% and 2.8% increase in two assessments respectively, however Chemistry students exam performance with music declined by 0.3% and 13.5% in both assessments respectively.